Radiolysis of NH3:CO ice mixtures – implications for Solar system and interstellar ices. Issue 2 (19th September 2020) - de Barros, A L F; Bergantini, A; Domaracka, A; Rothard, H; Boduch, P; da Silveira, E F
ABSTRACT: Experimental results on the processing of NH3:CO ice mixtures of astrophysical relevance by energetic (538 MeV 64 Ni 24+ ) projectiles are presented. NH3 and CO are two molecules relatively common in interstellar medium and Solar system; they may be precursors of amino acids. 64 Ni ions may be considered as representative of heavy cosmic ray analogues. Laboratory data were collected using mid-infrared Fourier transform spectroscopy and revealed the formation of ammonium cation (NH$_4^+$ ), cyanate (OCN − ), molecular nitrogen (N2 ), and CO2 . Tentative assignments of carbamic acid (NH2 COOH), formate ion (HCOO − ), zwitterionic glycine (NH$_3^+$ CH2 COO − ), and ammonium carbamate (NH$_4^+$ NH2 COO − ) are proposed. Despite the confirmation on the synthesis of several complex species bearing C, H, O, and N atoms, no N–O-bearing species was detected. Moreover, parameters relevant for computational astrophysics, such as destruction and formation cross-sections, are determined for the precursor and the main detected species. Those values scale with the electronic stopping power ( S e ) roughly as σ ∼ a S $_ e^n$, where n ∼ 3/2. The power law is helpful for predicting the CO and NH3 dissociation and CO2 formation cross-sections for other ions and energies; these predictions allow estimating the effects of the entire cosmic ray radiation field.